Human capital development and performance management as determinants of productive employee performance in public population services - Ramahzaleni Ramahzaleni; Ervin Nora Susanti; Firdaus Hamta (Journal of Applied Business Administration, 2026)
This study analyzes the contribution of human capital development factors (training, mentoring, coaching) and performance management factors (performance appraisal, reward system) toward productive employee performance at the Department of Population and Civil Registration (Disdukcapil) of Batam City. Drawing on Human Capital Theory, Competency Theory, Performance Management Theory, and the Two-Factor Theory of Motivation, this study argues that sustainable productive performance requires the simultaneous integration of capability development and motivational reinforcement. An explanatory quantitative design with census (saturated sampling) technique was employed, involving all 100 Disdukcapil employees as respondents. Data were collected through validated 5-point Likert scale questionnaires and analyzed using Multiple Linear Regression with classical assumption tests. The results indicate that, simultaneously, the five variables contribute significantly to productive performance (Adjusted R² = 0.766; F = 69.40; p < 0.001). Partially, all five variables showed positive and significant effects. The Reward System was found to be the most dominant factor (β = 0.312; t = 4.512; p < 0.001), followed by Training (β = 0.245; t = 3.124; p = 0.002). These findings suggest that in the compliance-oriented Indonesian public sector, extrinsic motivational drivers exert stronger immediate effects on productivity than capability development alone, highlighting the need for integrated HRM strategies that balance recognition-based motivation with continuous competency enhancement.